Prediction of Cooking Oil Production Amount Using the Fuzzy Time Series Ruey Chyn Tsaur Method - Rahmawati, Rahmawati; Fitri Ramadani, Annisa (Mathematical Journal of Modelling and Forecasting, 2023)
Cooking oil is used as a medium for frying foodstuffs that are widely consumed by the general public. Cooking oil can be produced from various raw materials, for example, coconut, copra, palm oil, soybeans, corn seeds, sunflower seeds, olive seeds, and others. This research aims to determine the predicted results of the amount of cooking oil production at PT. Pulau Sambu Kuala Enok and find out the results of forecasting the amount of cooking oil production at PT. Pulau Sambu Kuala Enok in 2023. The method used in this research is Ruey Chyn Tsaur's Fuzzy Time Series. Based on the results of data processing, forecasting results were obtained for January to December 2022 and this forecast has a MAPE value of 17.25%. The research results show that the Fuzzy Time Series Ruey Chyn Tsaur method has a good level of accuracy for predicting the amount of cooking oil production.